Analisis Ketepatan Penghitung Frekuensi dengan Metode Pencacahan Berbasis Mikrokontroler - Kurniawan, Freddy; Basukesti, Agus (Semesta Teknika, 2008)
A frequency counter is an electronic instrument, or component of one, that is used for measuring frequency. Frequency counters usually measure the number of oscillations or pulse per second in a repetitive electronic signal. A digital-signal frequency counter, can measure the number of positive-going-transition or the number of negative-going-transition of signal in a set of period time. This microcontroller-based frequency counter work by using a counter, which accumulates the number of negative-going-transitions occurring within two periods for 16-bit microcontroller-timer overflow. After the period, the value in the counter is divided by the period and transferred to a display. This frequency counter can measure frequency from 100 Hz to 1 MHz. The upper limit of frequency can be extended up to 256 MHz by adding a frequency divider. The analysis of the accuracy of measuring presented in this article can support to determine the number of digit to display. Â